Short‐term effects of soil texture, biochar, manure, and tillage practices on warm‐climate forage yields and nutrient content - Cade P. Cooper; James P. Muir; Kimberly B. Wellmann; Eunsung Kan; Lisandro J. Entio; Jeff A. Brady; Katherine Hays; Jaehak Jeong (Grassland Research)
Abstract Background Biochar (BC) amendment to soils can affect crop yields negatively, especially during the first season following application, by binding essential nutrients; however, little data exist on its effects on warm‐climate forage yields and nutritive values. We determined the effects of BC (0, 5, 10 Mg DM ha−1), dairy manure (0 and 10 Mg DM ha−1), soil type (loamy sand, sandy loam, clay loam), and tillage practices (till [incorporation of soil amendments with tillage] vs. no till [soil amendments surface application]) on the nutrient profile and dry matter yield (DMY) of Bermudagrass (Cynodon dactylon (L.) Pers.), maize (Zea mays L.), and sorghum‐Sudan (Sorghum drummondii (Nees ex Steud.) Millsp. & Chase). Methods Bermudagrass was harvested at the boot stage, sorghum‐Sudan when the canopy reached 90% light interception, and the maize 90–120 days after planting as silage. Samples were dried and analyzed for nutrients and DMY. Results BC and manure application were not detrimental to forage production or nutritive value to cattle in the first growing season. Conclusions Effects varied across tillage and soil type; thus, it is essential to consider soil texture and nutrient makeup before choosing the proper tillage and amendments. Longer study periods may produce different results since, over time, BC can act as a slow‐release source of nutrients.